2012
DOI: 10.1124/jpet.112.200444
|View full text |Cite
|
Sign up to set email alerts
|

Role of Prostaglandin Receptor EP2 in the Regulations of Cancer Cell Proliferation, Invasion, and Inflammation

Abstract: Population studies, preclinical, and clinical trials suggest a role for cyclooxygenase-2 (COX-2, PTGS2) in tumor formation and progression. The downstream prostanoid receptor signaling pathways involved in tumorigenesis are poorly understood, although prostaglandin E2 (PGE 2 ), a major COX-2 metabolite which is usually upregulated in the involved tissues, presumably plays important roles in tumor biology. Taking advantage of our recently identified novel selective antagonist for the EP2 (PTGER2) subtype of PGE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
107
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(110 citation statements)
references
References 50 publications
3
107
0
Order By: Relevance
“…The novel EP2 potentiator TG3-95-1 (referred to as compound 1 in Ref. 27) and EP2 antagonist TG4-155 were synthesized in our laboratory (27)(28)(29). All plasticware and reagents were endotoxin-free.…”
Section: Methodsmentioning
confidence: 99%
“…The novel EP2 potentiator TG3-95-1 (referred to as compound 1 in Ref. 27) and EP2 antagonist TG4-155 were synthesized in our laboratory (27)(28)(29). All plasticware and reagents were endotoxin-free.…”
Section: Methodsmentioning
confidence: 99%
“…The most significantly activated regulator, however, was PTGER2, which promotes tumor cell proliferation as well as invasion and angiogenesis. 34 This finding was unexpected, and indicates that immune mechanisms are activated in tumors of higher grade. The observation may be exploited clinically, as COX2 inhibitors and selective PTGER2 inhibitors are available for targeting of PTGER2 in tumors.…”
Section: Modern Pathology (2016) 29 616-629mentioning
confidence: 98%
“…The observation may be exploited clinically, as COX2 inhibitors and selective PTGER2 inhibitors are available for targeting of PTGER2 in tumors. 34 Small intestinal neuroendocrine tumors are characterized by recurrent chromosomal alterations, the most frequent involving loss of chromosome 18. Chromosomal gains involving chromosomes 4, 5, 7, 14 and 20 are observed in a small proportion of tumors and have been associated with shorter survival.…”
Section: Modern Pathology (2016) 29 616-629mentioning
confidence: 99%
“…When Jiang and Dingledine activated EP2 it promoted prostate cancer cell growth and invasion as well as upregulating tumor-promoting inflammatory cytokines like IL-6 (Jiang and Dingledine, 2013). Also, when Kambe et al inhibited EP4 expression, suppression in glioma cell growth was observed (Kambe et al, 2009).…”
Section: The Confirmed Presence Of the Pgd 2 Synthesis Pathwaymentioning
confidence: 99%
“…The presence of EP2 and EP4 is significant because it implies that even if PGD 2 is capable of anti-tumorigenic activity through its DP1 receptor, the abundance of PGE 2 could easily mask PGD 2 's impact by activating EP2 and EP4 signaling pathways. Looking to selectively block the PGE 2 /EP2 and PGE 2 /EP4 signaling pathways via small molecule antagonists might present a novel therapy for GBM development (Jiang and Dingledine, 2013).…”
Section: The Confirmed Presence Of the Pgd 2 Synthesis Pathwaymentioning
confidence: 99%